Method for preparing ethyl acetate by dehydrogenation condensation of ethanol
By using a heterogeneous copper acid-base bifunctional catalyst to carry out the ethanol dehydrogenation condensation reaction, the problems of catalyst toxicity and low ethanol conversion in the prior art were solved, and efficient and environmentally friendly preparation of ethyl acetate was achieved.
Patent Information
- Application Number
- CN202111401014.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-11-24
AI Technical Summary
In the existing ethyl acetate preparation method, the catalyst is toxic and the ethanol conversion rate is low, making it difficult to meet the market demand and environmental protection requirements.
The multiphase copper acid-base dual-function catalyst is used to carry out ethanol dehydrogenation reaction through a fixed bed reactor. The catalyst consists of active Cu and acid-base metal oxides, and the reaction temperature is 220-350°C.
The preparation of ethyl acetate with high selectivity (up to 95%) and high conversion (up to 75%) is achieved. The catalyst is non-toxic, has good stability and has a long lifespan.
Smart Images

Figure BDA0003371522520000081 
Figure BDA0003371522520000091
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing ethyl acetate, in particular to a method for preparing ethyl acetate by using ethanol as a reactant through a direct dehydrogenation condensation process. Background Art
[0002] Ethyl acetate is one of the most widely used fatty acid esters. It has excellent solubility and is a fast-drying, important green industrial solvent. It is widely used in the production of chemical products such as acetate fiber, ethyl fiber, chlorinated rubber, vinyl resin, synthetic rubber, coatings and paints; as an industrial solvent, it is used in coatings, adhesives, ethyl cellulose, artificial leather, linoleum colorants and artificial fibers; as an adhesive, it is used in the production of printing inks and artificial pearls; as an extractant, it is used in the production of products such as medicines and organic acids; as a spice raw material, it is the main raw material for fruit flavors such as pineapple, banana and strawberry, and spices such as whiskey and cream.
[0003] The production method of ethyl acetate is still mainly based on the traditional esterification method. Although large domestic methanol carbonylation acetic acid companies or companies with bioethanol devices provide abundant and cheap acetic acid and ethanol raw materials, the esterification process still has many disadvantages such as low utilization rate of acetic acid and environmental unfriendliness. Although the production process is relatively mature, the technical threshold is low, and the process and production technology are stable, the existing technology is increasingly unable to meet the demand, whether from the perspective of market demand or the interests of manufacturers. Therefore, it is of practical significance to develop an ethyl acetate production process with high efficiency, energy saving and low environmental load. The route of preparing ethyl acetate by ethanol dehydrogenation condensation is highly economical and environmentally friendly, and is an ideal route for preparing ethyl acetate. The ethanol dehydrogenation condensation method uses ethanol as raw material and synthesizes ethyl acetate by one-step dehydrogenation through gas-solid phase reaction. It has the advantages of simple process, green process, and easy separation of product and catalyst. In 2001, Davy Company used toxic copper-chromium catalyst to carry out the reaction of ethanol dehydrogenation condensation to prepare ethyl acetate. The selectivity of ethyl acetate was about 94%, but the ethanol conversion rate was only about 27%. The copper-zinc-aluminum-zirconium catalyst used by Japan National Petroleum Corporation has an ethyl acetate selectivity of 90-95%, but an ethanol conversion rate of 45%.
[0004] Although the above catalysts achieve the production of ethyl acetate by dehydrogenation condensation of ethanol, the catalysts used are either toxic or have low ethanol conversion rates. Therefore, it is of great significance to develop a non-toxic, easily available, highly reactive and selective solid catalyst system. Summary of the invention
[0005] The significance of the invention is that it overcomes the shortcomings of the current process of preparing ethyl acetate by direct dehydrogenation condensation of ethanol. The preparation method has a simple reaction process, a non-toxic catalyst, high selectivity for ethyl acetate, good stability and long life.
[0006] The ethyl acetate involved in the present invention is prepared by the following scheme.
[0007] Ethanol is used as a raw material, and a reaction is carried out in a fixed bed reactor. After a multiphase copper-based acid-base bifunctional catalyst is filled in a reaction tube, the reaction tube is placed in a fixed bed reactor, and the reaction temperature is 220-350°C. The copper-based acid-base bifunctional catalyst is composed of active Cu and acid-base metal oxides; the copper-based acid-base bifunctional catalyst, wherein the acidic metal oxide is one, two or more of zirconium oxide, yttrium oxide, ytterbium oxide, indium oxide, tungsten oxide, scandium oxide, tantalum oxide, niobium oxide, gallium oxide, tin oxide, and aluminum oxide; the basic oxide is one, two or more of zinc oxide, cerium oxide, lanthanum oxide, praseodymium oxide, magnesium oxide, and strontium oxide. The copper-based acid-base bifunctional catalyst, wherein the active metal Cu content is 5wt% to 35% (by weight). The copper-based acid-base bifunctional catalyst, wherein the active metal Cu content is preferably 10wt% to 25% (by weight). The acidic metal content is: 45wt% to 90wt% (based on weight calculation). The catalyst bed in the reaction tube has a thickness of 5 cm to 30 cm, the reaction is carried out at normal pressure, and the mass space velocity of the ethanol feed is 0.5 to 3.5 h -1 The preferred reaction conditions are: the catalyst bed thickness in the reaction tube is 10 cm to 25 cm, the ethanol feed mass space velocity is 0.5 to 3.5 h -1 The ethanol can be anhydrous ethanol or ethanol aqueous solution, and the water content is 1.0% to 10% (by weight). The reaction temperature of the ethanol dehydrogenation condensation to produce ethyl acetate is 220 to 260°C.
[0008] The preparation of ethyl acetate by ethanol dehydrogenation condensation catalyzed by a heterogeneous copper-based acid-base bifunctional catalyst has the following characteristics: (1) The introduction of active Cu promotes the dehydrogenation of ethanol; (2) The suitable Lewis sites on the surface of the oxide support are derived from the coordinated unsaturated metal ions on the surface. On the one hand, such sites interact with the active Cu species to transfer electrons, which not only disperses the active Cu species, avoids the sintering of Cu ions during the reaction and improves the stability, but also partially inhibits the dehydrogenation activity of Cu, avoids the excessive dehydrogenation of ethanol, and thus improves the dehydrogenation selectivity; (3) The balance of acid and base in the heterogeneous copper-based acid-base bifunctional catalyst is crucial. Excessive acidity triggers the ethanol dehydration side reaction; excessive alkalinity triggers excessive dehydrogenation, causing the decomposition of ethanol; the balance of acid and base sites can promote the condensation of acetaldehyde obtained by ethanol dehydrogenation with ethanol to form hemiacetal, and then dehydrogenate to obtain ethyl acetate. Among them, the combination and content of metal oxides in the heterogeneous copper-based acid-base bifunctional catalyst are crucial factors.
[0009] The advantages of this method are: (1) The multiphase copper-based acid-base bifunctional catalyst catalyzes the dehydrogenation condensation of ethanol to produce ethyl acetate. The catalyst preparation is simple and the catalyst catalyzes the reaction efficiently. The catalyst activation and regeneration can be completed by simple roasting and reduction operations. (2) The process of catalyzing the dehydrogenation condensation of ethanol to produce ethyl acetate by this catalytic system shows certain advantages, with the selectivity of the target product reaching 95%, the conversion rate reaching up to 75%, and the simultaneous co-production of hydrogen. DETAILED DESCRIPTION
[0010] In order to further explain the present invention in detail, several specific implementation cases are given below, but the present invention is not limited to these embodiments.
[0011] The reaction is carried out in a fixed bed reactor, and the reaction tube is filled with a catalyst and then placed in the fixed bed reactor;
[0012] Example 1
[0013] The preparation of 10wt% Cu-80wt% ZrO2-10wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 5.0g of cerium nitrate hexahydrate and 30.0g of zirconium oxynitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-80wt% ZrO2-10wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed. The raw material is 5% ethanol aqueous solution (weight concentration, the same below), and the mass space velocity is 1.5h -1The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0014] Example 2
[0015] The preparation of 10wt% Cu-80wt% In2O3-10wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 5.0g of cerium nitrate hexahydrate and 34.6g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and then calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-80wt% In2O3-10wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0016] Example 3
[0017] The preparation of 10wt% Cu-80wt% In2O3-10wt% PrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 5.0g of praseodymium nitrate hydrate and 34.6g of indium nitrate hydrate, dissolve them in 200ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and then calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-80wt% In2O3-10wt% PrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0018] Example 4
[0019] The preparation of 10wt% Cu-10wt% La2O3-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 30.0g of zirconium oxynitrate, 5.4g of hydrated lanthanum nitrate and 15.0g of zirconium oxynitrate, dissolve them in 200ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and then calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% La2O3-80wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0020] Example 5
[0021] The preparation of 10wt% Cu-10wt% ZnO-80wt% ZrO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 7.3g of zinc nitrate hexahydrate and 15.0g of zirconium oxynitrate, dissolve them in 200ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% Sn-80wt% ZrO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0022] Example 6
[0023] The preparation of 10wt% Cu-10wt% SrO-80wt% Y2O3 adopts the co-precipitation method. The specific operation is as follows: weigh 3.0g of copper nitrate trihydrate, 54g of yttrium nitrate hexahydrate and 4.1g of strontium nitrate, dissolve them in 200ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% SrO-80wt% Y2O3 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0024] Example 7
[0025] The preparation of 5wt%Cu-84wt%In2O3-11wt%CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 3.8g of copper nitrate trihydrate, 5.5g of cerium nitrate hexahydrate and 36.3g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 5wt%Cu-84wt%In2O3-11wt%CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0026] Example 8
[0027] The preparation of 20wt% Cu-71wt% In2O3-9wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 15.2g of copper nitrate trihydrate, 4.5g of cerium nitrate hexahydrate and 30.7g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 20wt% Cu-71wt% In2O3-9wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0028] Example 9
[0029] The preparation of 10wt% Cu-80wt% In2O3-10wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 5.0g of cerium nitrate hexahydrate and 34.6g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and then calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-80wt% In2O3-10wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 240°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0030] Example 10
[0031] The preparation of 10wt% Cu-80wt% In2O3-10wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 5.0g of cerium nitrate hexahydrate and 34.6g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and then calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-80wt% In2O3-10wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 220°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0032] Embodiment 11
[0033] The preparation of 10wt% Cu-80wt% In2O3-10wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 5.0g of cerium nitrate hexahydrate and 34.6g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-80wt% In2O3-10wt% CeO2 catalyst. Screen the catalyst with a mesh size of 14-25 and fill it into the reaction tube, fill a 10cm bed, the raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1The reaction was carried out at 220°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0034] Example 12
[0035] The preparation of 10wt% Cu-80wt% In2O3-10wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 5.0g of cerium nitrate hexahydrate and 34.6g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and then calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-80wt% In2O3-10wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 20cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 220°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0036] Example 13
[0037] The preparation of 10wt% Cu-45wt% In2O3-45wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 22.5g of cerium nitrate hexahydrate and 19.5g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and then calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-45wt% In2O3-45wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 220°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0038] Embodiment 14
[0039] The preparation of 10wt% Cu-70wt% In2O3-20wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 10.0g of cerium nitrate hexahydrate and 30.3g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-70wt% In2O3-20wt% CeO2 catalyst. Screen the catalyst with 14-25 mesh and fill it into the reaction tube, fill with 10cm bed, the raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 220°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0040] Embodiment 15
[0041] The preparation of 10wt% Cu-80wt% In2O3-10wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 5.0g of cerium nitrate hexahydrate and 34.6g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-80wt% In2O3-10wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 10cm bed layer. The raw material is 10% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 220°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0042] Example 16
[0043] The preparation of 10wt% Cu-80wt% In2O3-10wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 5.0g of cerium nitrate hexahydrate and 34.6g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-80wt% In2O3-10wt% CeO2 catalyst. Screen the catalyst with a mesh size of 14-25 and fill it into the reaction tube, fill with a 10cm bed, the raw material is anhydrous ethanol, and the mass space velocity is 1.5h -1The reaction was carried out at 220°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0044] Embodiment 17
[0045] The catalyst used in Example 2 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 15cm bed layer. The raw material was 5% ethanol aqueous solution, and the mass space velocity was 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0046] Embodiment 18
[0047] The catalyst used in Example 17 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 15cm bed layer. The raw material was 5% ethanol aqueous solution, and the mass space velocity was 1.5h -1 The reaction was carried out at 230°C. After 8 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0048] Embodiment 19
[0049] The catalyst used in Example 18 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 15cm bed. The raw material was 5% ethanol aqueous solution, and the mass space velocity was 1.5h -1 The reaction was carried out at 230°C. After 10 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0050] Embodiment 20
[0051] The catalyst used in Example 19 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 15cm bed. The raw material was 5% ethanol aqueous solution, and the mass space velocity was 1.5h -1 The reaction was carried out at 230°C. After 18 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0052] Comparative Example 1
[0053] The preparation of 10wt% Cu-90wt% In2O3 adopts the co-precipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate and 38.9g of hydrated indium nitrate, dissolve them in 200ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filter and wash with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-90wt% In2O3 catalyst. Screen the catalyst with 14-25 mesh and fill it into the reaction tube, fill with 15cm bed, the raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0054] Comparative Example 2
[0055] The preparation of 10wt% Cu-90wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate and 45.0g of cerium nitrate hexahydrate and dissolve them in 200ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-90wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0056] Comparative Example 3
[0057] The preparation of 10wt% Cu-10wt% In2O3-80wt% CeO2 adopts the coprecipitation method. The specific operation is as follows: weigh 7.6g of copper nitrate trihydrate, 40.0g of cerium nitrate hexahydrate and 4.3g of hydrated indium nitrate, dissolve them in 200 ml of water, and adjust the pH value to 10 with NaOH (3mol / L) aqueous solution. Aging and stirring in an 80℃ oil bath for 2h, filtering and washing with water until neutral. Dry at 80℃ overnight, and then calcine at 500℃ N2 for 3h (nitrogen flow rate is 30ml / min) to obtain 10wt% Cu-10wt% In2O3-80wt% CeO2 catalyst. The 14-25 mesh catalyst is sieved and filled into the reaction tube, filling a 15cm bed layer. The raw material is 5% ethanol aqueous solution, and the mass space velocity is 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.
[0058] Appendix 1. Reaction results of ethanol dehydrogenation condensation to prepare ethyl acetate catalyzed by copper-based acid-base bifunctional catalyst
[0059]
[0060]
[0061] The results show that the composition and content of each component of the multiphase copper-based acid-base bifunctional catalyst are key factors affecting the reaction effect. The appropriate content of Cu sites and acid-base sites is the key to achieving high selectivity catalysis. The lack of acid sites or basic sites or inappropriate ratios will cause a mismatch in reaction rate, resulting in a significant decrease in the selectivity of the target product ethyl acetate. In addition, reaction temperature, space velocity and other conditions also affect the reaction effect.
Claims
1. A method for preparing ethyl acetate by dehydrogenation condensation of ethanol, characterized in that: The process of preparing ethyl acetate by dehydrogenation condensation of ethanol is as follows: using ethanol as a raw material, reacting in a fixed bed reactor at a reaction temperature of 220-350°C; The heterogeneous copper-based acid-base bifunctional catalyst is composed of active Cu and acid-base metal oxides. The copper-based acid-base bifunctional catalyst, wherein the acidic metal oxide is one, two or more of yttrium oxide, ytterbium oxide, indium oxide, tungsten oxide, scandium oxide, tantalum oxide, niobium oxide, gallium oxide, and tin oxide; The basic oxide is one, two or more of cerium oxide, lanthanum oxide, praseodymium oxide, magnesium oxide and strontium oxide. The copper-based acid-base bifunctional catalyst, wherein the active metal Cu content is 5% to 10% by weight; The mass ratio of acidic oxide to basic oxide is 1:1~10:
1.
2. The method according to claim 1, characterized in that: The mass ratio of acidic oxide to basic oxide is 4:1~8:
1.
3. The method according to claim 1, characterized in that: The catalyst bed thickness is 5 cm to 30 cm, the reaction is at normal pressure, and the feed mass space velocity of ethanol is 0.5 to 3.5 h -1 .
4. The method according to claim 1 or 3, characterized in that: The reaction conditions are as follows: the catalyst bed thickness in the reaction tube is 10 cm to 25 cm, and the mass space velocity of ethanol feed is 1.0 to 2.0 h -1 .
5. The method according to claim 1 or 3, characterized in that: The ethanol is anhydrous ethanol or an ethanol aqueous solution, and the water content is 1.0% to 10% by weight.
6. The method according to claim 1, characterized in that: The reaction temperature of the ethanol dehydrogenation condensation to produce ethyl acetate is 220-260°C.
7. The method according to claim 1, characterized in that: The multiphase copper-based acid-base bifunctional catalyst is prepared by coprecipitation of Cu, acidic oxides and corresponding soluble salts of basic oxides in a solution.
Citation Information
Patent Citations
Catalyst for ester production and process for producing ester
US20040242917A1